THE PROTECTION OF ECONOMIC RIGHTS TOWARDS PERSON WITH COLOR BLINDNESS BASED ON INTERNATIONAL LAW - Dwi Pragasa Ananda; Azhari Yahya (Fakultas Hukum Universitas Syiah Kuala, 2018)
Improvement of economy and development are carried out by the Indonesian government in many ways. The spread of employment each year is a real example of performance by the Indonesian government for all Indonesian to improve welfare of their life. However, this way does not provide sufficient results against those who are categorized as person with color blindness (daltonism). As a state of law, government of Indonesia should uphold human rights in the society. However, in fact the case that led to deprivation of economic rights of people with color blindness to find employment is not in line with the real expectation. The purposes of this thesis are to explain the protection of economic rights against color blind people in Indonesia who are deprived of freedom in an effort to get a job; to identify and explain how international and national law governing economic rights people with color blindness in Indonesia and also to explain the legal sanction that can be applied. This research uses normative research (normative legal research). Normative research is a legal doctrinal research or legal research theory, which uses primary, secondary and tertiary legal resources including academic paper, research report, dictionary etc. The result shows that the condition in Indonesia related to the deprivation of economic rights against color blindness people in an attempt to find a job based on international conventions is considered as discrimination. Until the year 2016 there are about four international conventions have been ratified by the government of Indonesia to protect their economic rights. Since 1999 Indonesia has become a country that promotes the Convention on Elimination of All Forms of Racial Discrimination Convention through the Law Number 29 of 1999 to eliminate discrimination. In 2008 the Indonesian government enacted the Law Number 40 of 2008 on The Elimination of Racial and Ethnic Disrcimation as a legal tool to apply criminal sanctions against the perpetrators of discrimination. It is suggested that in order to achieve national goals which protect all the people of Indonesia. The government of Indonesia is recommended to keep control and apply these laws in the society. By doing so human rights can be fully fulfilled and discrimination doesn't appears again. Then, government of Indonesia should consistent and aware of the importance of respecting other rights.